2021
DOI: 10.3390/ph14121313
|View full text |Cite
|
Sign up to set email alerts
|

Promising Antiviral Activity of Agrimonia pilosa Phytochemicals against Severe Acute Respiratory Syndrome Coronavirus 2 Supported with In Vivo Mice Study

Abstract: The global emergence of the COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has focused the entire world’s attention toward searching for a potential remedy for this disease. Thus, we investigated the antiviral activity of Agrimonia pilosa ethanol extract (APEE) against SARS-CoV-2 and it exhibited a potent antiviral activity with IC50 of 1.1 ± 0.03 µg/mL. Its mechanism of action was elucidated, and it exhibited a virucidal activity and an inhibition of viral adsorption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…It was analyzed using an ExionLC TM AD UPLC and a TripleTOF 5600+ Tandem Mass Spectrometer (AB SCIEX). They adopted the criteria described previously [ 55 , 56 ]. To identify compounds, PeakView 2.2 with the MasterView 1.1 software (AB SCIEX) was used to compare m / z values obtained by MS and MS 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It was analyzed using an ExionLC TM AD UPLC and a TripleTOF 5600+ Tandem Mass Spectrometer (AB SCIEX). They adopted the criteria described previously [ 55 , 56 ]. To identify compounds, PeakView 2.2 with the MasterView 1.1 software (AB SCIEX) was used to compare m / z values obtained by MS and MS 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Various studies reported that NTZ could inhibit the replication of canine CoV-S378, bovine CoV, murine CoV, and human enteric CoV. Both NTZ and its active metabolite inhibit MERS-CoV cultured in LLC-MK2 cells [ 23 , 24 ].…”
Section: Ntz and Covid-19mentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus (SARS-CoV-2) was primarily documented as the probable cause of acute respiratory infection in Wuhan, Hubei province of China in late December 2019 (Al-Kuraishy et al 2021 ). The World Health Organization (WHO) designated this infection as coronavirus disease 2019 (COVID-19) (Attallah et al 2021 ). SARS-CoV-2 utilizes angiotensin-converting enzyme type 2 (ACE2) as an entry point (Al-Kuraishy et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%